Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Perilaku Kerja Inovatif Guru Di SMA Swasta Se-Kecamatan Pamijahan Bogor - Nurdin Fahrurrobi; Muzhir Ihsan; Ima Rahmawati; Hana Lestari (PUSAT SAINS INDONESIA, 2020)
Innovative work behavior is an individual action to recognize a problem, bring up new ideas, develop new ideas, and realize each idea or ideas with techniques and procedures that are new and useful for the organization. This study aims to explain the influence of transformational leadership and organizational culture on innovative work behavior of teachers. This research was conducted in private high schools in Pamijahan District, Bogor Regency. The number of samples taken was 110 teachers, using a probability sampling method with the proportionate stratified random sampling technique. The research method used is quantitative research with data collection techniques using a questionnaire or questionnaire. The data analysis technique used is multiple linear regression. Based on the results of the analysis it was found that transformational leadership and organizational culture simultaneously positively influenced the innovative work behavior of teachers. This shows that the stronger the influence of transformational leadership and organizational culture simultaneously (together), the more innovative work behavior produced by the teacher will be higher. Therefore, to foster innovative work behavior in teachers is expected to pay more attention to transformational leadership and organizational culture to improve teacher's innovative work behavior.